30-day mortality following trauma and orthopaedic surgery during the peak of the COVID-19 pandemic: a multicentre regional analysis of 484 patients. (13th July 2020) - Karayiannis, Paul N.; Roberts, Veronica; Cassidy, Roslyn; Mayne, Alistair I. W.; McAuley, Daryl; Milligan, David J.; Diamond, Owen
Abstract : Aims: Now that we are in the deceleration phase of the COVID-19 pandemic, the focus has shifted to how to safely reinstate elective operating. Regional and speciality specific data is important to guide this decision-making process. This study aimed to review 30-day mortality for all patients undergoing orthopaedic surgery during the peak of the pandemic within our region. Methods: This multicentre study reviewed data on all patients undergoing trauma and orthopaedic surgery in a region from 18 March 2020 to 27 April 2020. Information was collated from regional databases. Patients were COVID-19-positive if they had positive laboratory testing and/or imaging consistent with the infection. 30-day mortality was assessed for all patients. Secondly, 30-day mortality in fracture neck of femur patients was compared to the same time period in 2019. Results: Overall, 496 operations were carried out in 484 patients. The overall 30-day mortality was 1.9%. Seven out of nine deceased patients underwent surgery for a fractured neck of femur. In all, 27 patients contracted COVID-19 in the peri-operative period; of these, four patients died within 30 days (14.8%). In addition, 21 of the 27 patients in this group had a fractured neck of femur, 22 were over the age of 70 years (81.5%). Patients with American Society of Anesthesiologists (ASA) grade > 3 and/or age > 75 years were at significantly higher risk of death if they contracted COVID-19 within the study period. Conclusion: Overall 30-day postoperative mortality in trauma and orthopaedic surgery patients remains low at 1.9%. There was no 30-day mortality in patients ASA 1 or 2. Patients with significant comorbidities, increasing age, and ASA 3 or above remain at the highest risk. For patients with COVID-19 infection, postoperative 30-day mortality was 14.8%. The reintroduction of elective services should consider individual patient risk profile (including for ASA grade). Effective postoperative strategies should also be employed to try and reduce postoperative exposure to the virus. Cite this article: Bone Joint Open 2020;1-7:392–397.